Enhanced Data Security in Video Media using RSA-LSB Hybrid Technique - Putra, Nafis Artaruna; Sidiq, Muhammad Fajar; Amrulloh, Arif (Universitas Hamzanwadi, 2025)
Securing structured documents in dynamic digital media such as video remains a challenge, especially under threats like unauthorized access, format conversion, and compression. This research aims to build a secure and hidden digital document insertion system into video media using a hybrid approach between RSA cryptography algorithm and Least Significant Bit (LSB) steganography. This research developed a steganography system using the prototype method to embed complex documents into video media securely. It uses Python with libraries like OpenCV and PyCryptodome, embedding data into the blue channel's LSB bit to maintain visual quality. The system was tested using various video samples and documents to ensure error-free embedding and 100% accurate extraction, with no file corruption. Robustness against compression and format conversion was also evaluated using metrics like PSNR, SSIM, and BER. The study successfully created a secure system for embedding complex digital documents into video media. Evaluation confirmed high visual quality (PSNR 45.3-63.2 dB), 100% data recovery, and resilience to post-processing, a significant advance over methods that handle only simple payloads.